INFLUENCE OF THE CYP3A4 ISOENZYME METABOLIC ACTIVITY AND CYP2C19 GENE POLYMORPHISMS ON CLOPIDOGREL ANTIPLATELET EFFECT IN PATIENTS WITH ACUTE CORONARY SYNDROME UNDERGOING PERCUTANEOUS CORONARY INTERVENTION - K. B. Mirzaev; R. E. Kazakov; V. V. Smirnov; D. A. Andreev; D. A. Sychev (Столичная издательская компания, 2015)
Aim. Carriership of CYP2C19*2 allelic variant and reduced CYP3A4 activity can affect the formation of clopidogrel's active metabolite and, respectively, its antiplatelet effect. We sought to determine the impact of CYP3A4 isoenzyme activity and CYP2C19 polymorphisms on platelet aggregation. Material and methods. The study included 81 patients with acute coronary syndrome (ACS) and subsequent percutaneous coronary intervention (PCI): 64 males and 17 females, mean age 63.9±10.9 years. CYP2C19 allelic variants were detected by the method of real-time polymerase chain reaction. CYP3A4 isoenzyme activity was estimated by urinary 6-β-hydroxycortisol/free cortisol ratio (6-OHC/FC) using the method of high-performance liquid chromatography. Platelet functional activity was evaluated by a portative aggregometer - the VerifyNow P2Y12 assay. Results. Logistic regression analysis has demonstrated significantly increased risk of clopidogrel resistance in patients-carriers of the CYP2C19*2 polymorphism (p=0.022). CYP2C19*2 non-carriers had significantly higher mean platelet inhibition percentage as compared with the carriers of this allele: 30.7±20.1 in the CYP2C19*1/*1 group vs 18.2±16.4 in the CYP2C19*1/*2 one (р=0.03). Clopidogrel laboratory resistance (P2Y12 Reaction Units (PRU)>208) was found out to be higher in the CYP2C19*2-carriers as compared with non-carriers: 53.8% in the patients with the CYP2C19*1/*2 genotype and 16.2% in subjects with the CYP2C19*1/*1 genotype (odds ratio [OR]=1.8; 95% confidence interval [95% CI]: 1.0-3.2; р=0.0067). Linear regression analysis has revealed that smaller mean diameter of stent slightly reduces the risk of clopidogrel resistance development. No significant distinctions in urinary 6-OHC/FC ratios (the marker of CYP3A4 activity) were observed: 3.4±2.8 in the PRU>208 group and 3.2±3.0 in the PRU<208 group (p=0.8). Besides, no significant correlation between platelet activity and the 6-OHC/FC ratio was found (р=0.84). Conclusion. CYP2C19*2-carriership in ACS patients undergoing PCI significantly increases the risk of clopidogrel laboratory resistance. The urinary 6-OHC/FC ratio (as a marker of CYP3A4 isoenzyme activity) does not correlate with platelett functional activity.